Oxyuriasis at the Department of Pediatrics, Dr. Pirngadi Hospital, Medan - Hasibuan, Berlian; Naim, Mahruzzaman; Lubis, Azwan H.; Pasaribu, Syahril; Lubis, Chairuddin P. (Paediatrica Indonesiana, 1989)
During the period of 3 months (February - April 1987), a prospective study on oxyuariasis among children had been conducted at Child Health Deparment of Dr. Pirngadi Hospital Medan. All children over 8 months of age were included in this study. The diagnosis was based on the modified Scoth 's technique. Oxyuriasis ova were found in 21 out 119 children (17,65%). The peak incidence was found in the school age.